Deciphering the genetic and epigenetic landscape of pediatric bithalamic tumors. (1st December 2021) - Tauziède‐Espariat, Arnault; Debily, Marie‐Anne; Castel, David; Grill, Jacques; Puget, Stéphanie; Roux, Alexandre; Saffroy, Raphaël; Gauchotte, Guillaume; Wahler, Ellen; Hasty, Lauren; Chrétien, Fabrice; Lechapt, Emmanuèle; et al.
Abstract : Pediatric bithalamic gliomas encompass several histomolecular tumoral types from benign to malignant and underlines the central role of a comprehensive neuropathological review, including immunohistochemistry, genetic, and epigenetic analyses, to achieve an accurate diagnosis.